Blockchain-based shop floor control system for small and medium-sized enterprise evolution to industry 4.0 - Chin-Te Lin (Scientific Reports)
Abstract Small and medium-sized enterprises (SMEs) require agile and robust strategies to navigate the difficulties of their evolution toward Industry 4.0. This study proposes a Blockchain-based Shop Floor Control System (BSFCS) that incorporates a Consensus-based Workflow Change Integration (CWCI) mechanism and Smart Contract Service (SCS) design methodology to provide these strategies. The CWCI represents an incremental agile approach, enabling real-time workflow adjustments and smooth, rapid integration of evolving enterprise requirements. The modular architecture and optimized key-state data structures that are features of the SCS design methodology support efficient transaction management, ensuring system feasibility. A prototype implementing the BSFCS was tested on a realistic industrial platform replicating real-world manufacturing conditions. Results from two validation experiments demonstrate significant performance improvements over a standard model. These enhancements include dynamic workflow adaptability, enhanced operational transparency, and efficient handling of real-time changes. These BSFCS characteristics represent requirements SMEs need for a reliable and sequential pathway they can follow implementing Industry 4.0. They show that compared to existing frameworks, the BSFCS framework we propose offers superior adaptability and scalability. It particularly excels in handling dynamic workflow changes and sequential upgrades with minimal disruption to ongoing operations.